Anticancer Screening of Quercetin as a Natural Treatment - Ahmed, Wedad (Scientific Journal for Faculty of Science-Sirte University, 2022)
Oxidation stress is a process that damages the cells of the body, and also leads to the happen of many diseases such as cancer. This disease is known among all ages in every part of the world. In cancer cells, increasing types of free radicals flaw the balance in the cell and thus increasing free radicals target all types of molecules, including proteins, lipids, and nucleic acids. If the body cannot produce enough antioxidants, increasing free radicals damage the cells of the body. The defect in apoptosis also prevents malignant cells from being damaged. This paper aims to study the effect and activity of quercetin as an antioxidant and anticancer drug in vitro. The mechanism of increasing free radical formation causing cell damage will be explained. This study also presents a discussion about the mechanism of apoptosis pathways using the MTT scale to measure the cell's ability to metabolic activity and whether the cells are still alive. The most significant shifts were for (Raji, MOLT-4 and CT-26 equal to 0.18 ± 0.09, 2.1 ± 0.9, and 5.5 ± 0.38, respectively. Apoptosis was detected using the BD Annexin V FITC assay and apoptosis was measured at (P < 0.001). Also, in vivo, the positive effects of different doses of quercetin on affected models are discussed.